CARA BIJAK PEMANFAATAN E-COMMERCE DI KALANGAN GEN Z PADA PERKEMBANGAN KEUANGAN DIGITAL - Evi julaenti; ERMA YAWANTI; TASYA ERTYANI; TATU MULYANTI; DWI FITRIANINGSIH; PUTRI WULANDARI (Prodi Akuntansi, Universitas Pamulang Kampus Serang, 2024)
E-commerce is one of the most popular platforms among Gen Z today as it is essential for them to fulfill their lifestyle. E-commerce offers a means to purchase a variety of needs, ranging from daily goods to services, and as a technological advancement in this modern era, it will certainly have an impact on many people, including Gen Z. This study uses the current era of globalization, the technological advancements generated by e-commerce will certainly have an impact on many people. In the current era of globalization, the technological advancements generated by e-commerce will certainly have an impact on many people. This research employs a quantitative approach. Utilizing this method, the researcher's goal was to collect comprehensive data on how many students of SMKN 1 Rangkasbitung used e-commerce.The purpose of this PKM activity is for the mitigation team to understand digital currency literacy. The way to use e- commerce in the Z community is through financial education, which helps generation Z understand money management, budgeting, and online transaction costs. Furthermore, by using technology in a responsible way, it is possible to fully utilize e-commerce, which can facilitate the combination of knowledge can facilitate the combination of technology, money, privacy, and social dynamics, helping Generation Z become responsible and conscious consumers. Keyword;generasi z e commerce